A BMI >35 does not protect patients undergoing cardiac bypass surgery from red blood cell transfusion. (January 2017) - Mongero, Linda B.; Tesdahl, Eric A.; Stammers, Al H.; Dickinson, Timothy A.; Kypson, Alan P.; Brown, John; Weinstein, Sam
The effect of obesity on allogeneic intraoperative blood product transfusion in patients undergoing coronary artery bypass graft surgery (CABG) is poorly understood. We analyzed the influence of obesity on the risk of intraoperative red blood cell (RBC) transfusion among 45, 200 consecutive non-reoperative CABG procedures from a multi-institutional perfusion database. A body mass index (BMI) in obese I category was associated with a 9.9% decrease in transfusion risk (p<0.05). Compared to patients with a normal BMI, obese I and obese III patients do not have any change in the relative risk of RBC transfusion. Overweight and mild obesity have a protective role in reducing intraoperative blood transfusion during cardiopulmonary bypass (CPB) surgery. However, logistic regression analysis showed that much of the observed reduction in transfusion rates for obese patients can be accounted for by other known confounds. The lack of a linear effect of increasing BMI on blood transfusion risk is a novel finding and warrants further investigation.